Effect of alkaline solution on compressive strength of cement laterized cube with different soil grains size - Mohamad Syafiq, Othman (2015)
There are many factors that can increase the compressive strength of cement laterized cube. For example, it can be affected by the influence of additives, mix ratio of materials, grains size of aggregates and many other factors. This paper report the effect of alkaline solution concentration on the compressive strength of cement laterized cube which made by different laterite soil grains size. Besides that, there were two curing method that has been carried out which were air curing method and also dry in oven method. This research is also with a view to recommending the production of blocks from cement laterized in supplementing sandcrete blocks in the building construction industry, especially for low cost or rural building. For sample preparations, the crushed laterite soil was sieved into three different grains sizes which are, 1.18mm, 600 micro and 150 micro sizes. Then, each soil sizes will be mixed with a mix ratio of 1:2:6 (cement: soil: sand). Sodium hydroxide, (NaOH) solution with concentration of 1, 2 and 3 molar will be added in the mix and then cast the cube samples for each curing method. The compressive strength of the cube samples were recorded at the age of 14 days and 28 days of curing. The effect and relationship between the soil grains size, alkaline solution concentration, and curing method can be seen clearly. It can be concluded that, for this soil sample and for the mix ratio of 1:2:6, only 1 mol of alkaline solution is recommended. Addition of higher concentration of alkaline solution will reduce the compressive strength of the cube. In term of grains size effect, control samples made from 600 micro sizes produce the highest average compressive strength which is 3.602 MPa and 3.745 MPa for air curing and oven dry curing respectively. With addition of 1 mol of NaOH, sample with grains size of 1.18 mm produce the highest average compressive strength of 4.364 Mpa and 4.035 MPa for air curing and oven dry curing respectively. In tem of curing method, the cube samples for each grains size which undergo air curing method produced higher strength than sample undergo oven dry method at the age of 28 days.